KARAKTER SANTRI DALAM BINGKAI SASTRA CENGKIR EL KHALIEQY - Sarno Hanipudin; Vikroturrohmah Vikroturrohmah (AT-THARIQ: Jurnal Studi Islam dan Budaya, 2021)
The interest in this theme in the background backs the loss a positive character on the students themselves, so intellectual that there is less balanced with good character and lead to reduced even loss of morality. Character is the nature of the human mind that affect all thought and behavior, while the students is a nickname for a student of religion. Interesting to see the character of students in the frame of literary, biographical novel Cengkir students Abidah El Khalieqy work, where the main character is a figure in it appointed Slamet Riyanto career which reached its highest level as Director General Hajj and Umrah Ministry of Religious Affairs of the Republic of Indonesia.Keywords: Caracter, Santri, Novel